Effect of Ethylene Concentration and Exposure Time on Physico-Chemical Quality and Colour Value of Sapota Fruit (Manilkara zapota) - Vidhya, M.; Pandiarajan, T.; Pandiselvam, R.; Amirtham, D.; Balakrishnan, M.; Haseena, R.; Nishashree, R. (Asian Journal of Chemistry, 2017)
A study was conducted to optimize the ethylene concentration and exposure time for the ripening of sapota fruit. The fruits were ripened in the metal chamber with three different ethylene concentration (50, 100 and 150 ppm) and exposure time (12, 24 and 36 h). The ethylene treated fruits were analyzed for the quality parameters viz., firmness, physiological loss in weight, pulp to peel ratio, total soluble solid, pH, colour values and organoleptic score. The fruits treated with 100 ppm ethylene concentration for an exposure time of 24 h ripened in 2 days had 2.75 N firmness, 4.1 % physiological loss in weight, 15.89 pulp to peel ratio, 4.93 pH, 24.6° Brix total soluble solid and L value of skin 36.84, a value of skin 8.3, b value of skin 8.3 and scored maximum overall acceptability value of 8.56.